Chemical and Organoleptic Characteristics of Cocoa Powder from Fermented and Unfermented Cocoa Beans from Masni District and Sidey in Manokwari Regency - Murtiningrum Murtiningrum; Isak Silamba; Parlindungan Sijabat; Sritina N P Paiki; Zita L Sarungallo (Indonesian Journal of Food Technology, 2023)
beverage industry, such as chocolate drinks and ingredients for cakes, puddings, and ice cream. The fermentation process of cocoa beans is one of the determining factors for the quality of cocoa powder products produced. This is because during the fermentation process, physical, chemical, and organoleptic characteristics are formed, which become the standard for high-quality cocoa powder products. One of the factors that influences the success of the cocoa bean fermentation process is the fermentation time. The right fermentation time is expected to produce high-quality cocoa beans with a distinctive chocolate flavor, according to consumer preferences. The aim of this study was to determine the chemical, and organoleptic characteristics of cocoa powder from cocoa beans originating from Masni District and Sidey District with different fermentation times. The study consisted of six treatments: cocoa beans processed by the community (BKT), cocoa beans without fermentation (BKTF), cocoa beans fermented for 3 days (BK3), 4 days (BK4), 5 days (BK5), and 6 days (BK6). The differences between the treatments of unfermented cocoa beans and the fermentation time affect the physicochemical and organoleptic characteristics of the resulting cocoa powder. The fermentation process tends to improve the color of cocoa powder from dark brown to a lighter shade of brown, increase the moisture content, decrease the fat content, and significantly influence the organoleptic characteristics. Fermenting cocoa beans for 5 days results in cocoa powder with the best physical, chemical, and organoleptic characteristics. The organoleptic test of cocoa powder from cocoa beans fermented 5 days (BK5) show a slightly light brown to brown color, a strong to very strong cocoa powder flavor, a taste from less bitter to moderately bitter, and acidity levels from less acidic to moderately acidic.